Evaluating Mathematics Curriculum of the Primary Fourth Grade in Kingdom of Saudi Arabia in The Light of STEM Integral Methodology - Almuntashri , Soha Sahlan; Almohammadi, Najwa Atyan (Journal of Curriculum and Teaching Methodology, 2022)
This research aims to identify the availability of STEM requirements in Math curriculum of the primary fourth grade in KSA. To achieve the study objectives, the researcher adopted the descriptive approach using content analysis method, as well as the researcher built a list of STEM requirements that must be included in Math curriculum of the primary fourth grade in KSA. This list is to be presented to a number of arbitrators to verify its reliability, and then to be transformed into content analysis card, which included (58) sub-requirements, divided into (5) main requirements as follows: (Objectives, Content, Instruction Methods & Strategies, Aids and Activities, and Evaluation). The content of Math textbooks of primary fourth grades in the first and second semester is analyzed after verifying consistency of this list, including (Student Book, Teacher Guide, Teacher’s Resources of Classroom Activities), 2020-2021 Edition. The study findings reached a list of evaluation the fourth primary grade math curriculum in KSA requirements in the light of STEM integrated strategy, including (58) sub-requirements, divided to five main requirements including (Objectives, Content, Instruction Methods & Strategies, Aids and Activities, and Evaluation) in the light of STEM integrated strategy. Moreover, Content analysis revealed low-grade availability of evaluation requirements of Math curriculum of the primary fourth grade in KSA in the light of STEM integrated methodology, whereas the availability of main requirements ranged from (46.76%) to (4.16%).